COMMERCIAL VEGETABLE SUPPLY CHAINS IN THE TRADITIONAL MARKET OF BOGOR CITY THAT GIVE TO FARMERS - Miftah, Himmatul; Yoesdiarti, Arti; Soka, Tiara Dewi (Universitas Djuanda Bogor, 2018)
The price gap between farmers and retailers in commercial vegetables like spinach, tomatoes, potatoes and shallots in Bogor City was predicted as a result from the high trading margin. The research aims to analyze income, margin and farmer share obtained by commercial vegetable supply chain actors in Bogor City. The study was conducted in March - October 2017 at the Bogor Traditional Market and the Jambu Traditional Market. The selection of respondents used the purposive sampling and snowball sampling method. Result shows that the R / C ratio of farmers is lower than that of traders. The R/C ratio received by farmers is 1,48, while that received by traders is 2,64. The average Farmer Share (41,2%) is lower than the seller share (58,8%). The average marketing margin is Rp 14,576.5. The supply chain that take side to farmers regarding to the value of R/C, the total margin and the farmers share value are found in potato commodities because it has a higher R / C ratio than traders, higher farmer shares than traders, and trading margin that lower than the three other commodities compared.